Impact of severity of adolescent idiopathic thoracic scoliosis on range of motionof neck and shoulder complex - MOHAMED FAWZY HELMY ABDEL-HAMID; SAMIR AHMED EL SABBAHI (2022)
(3GLQjJ gPg GdOQGSI aj YjGOGJ GdYdGL GdWHjYj HGdbGgQI GdcHQj aj GdaJQI ef CcJhHQ (B2020 (3Gdj jfGjQ (B2022 (3deYQaI JCKjQ GdLfa GdUOQj ZjQ eYdhe GdSHH aj GdeQGgbjf Ydj GdeOj GdMQcj deaUd GdcJa hGdQbHI(B. (3eGFI hYTQhf TNUG ef GdLfSjf Je JbSjege Gdj eLehYJjf cGdJGdj(B: (3eLehYg GdOQGSI (B((3C(B): 20 (3eQjVG jYGfhf ef GdLfa GdUOQj hRGhjI GdLfa GdUOQj ef (B10 (3Gdj (B20 (3OQLI(B. (3eLehYI GdOQGSI (B((3H(B) : 20 (3eQjVG jYGfhf ef GdLfa GdUOQj hRGhjI GdLfa GdUOQj ef (B20 (3Gdj (B40 (3OQLI(B. (3eLehYI GdOQGSI (B((3L(B) : 20 (3eQjVG jYGfhf ef GdLfa GdUOQj hRGhjI GdLfa GdUOQj CcKQ ef (B40 (3OQLI(B. (3GdeLehYI GdVGHWI (B((3O(B) : 60 (3eQjVG dG jYGfhf ef GdLfa GdUOQj(B. (3JJhGaQ ajge GdTQhW GdJGdjI(B: 1. (3dG jYGfhf ef BdGe eRefI aj GdYehO GdabQj (B. 2. (3GYeGQge eG Hjf (B12 (3YGeG Gdj (B18 (3YGeG (B. 3. (3RGhjg GdLfa GdUOQj ef (B10 (3OQLGJ Gdj (B50 (3OQLI (B. (3hbO GSaQJ GdfJGFL Yf(B: (3hLhO JCKjQ SdHj ddLfa GdUOQj Ydj GdeOj GdMQcj deaUd GdcJa hGdQbHI aj GdeQGgbjf GdPjf jYGfhf ef GdLfa GdUOQj ZjQ eYdhe GdSHH(B.s
Thesis (M.Sc.)-Cairo University,2022.
Bibliography: p. 71-86.
Keywords: Physical Therapy; shoulder flexion and abduction